A CONVERSATION ANALYSIS ON THE INTERVIEW BETWEEN ELLEN DEGENERES AND HILLARY CLINTON - Lilis Uli Artha; Ridwan Hanafiah; Matius C.A Sembiring (Institut Pendidikan Tapanuli Selatan, 2023)
This research aims to find out the aspects of conversational nteractions in the interview, to analyze how those aspects of conversational interactions realized in the interview and to explain why those aspects of conversational interactions are realized in the interview. This research investigates the aspects of conversational interactions of conversation analysis based on Brian Paltridge‘s perspective. The research method used is descriptive qualitative. The main data of the research are the utterances which is a script between the interviewer (Ellen Degeneres) and the interviwees (Hillary Clinton). The source of data is video of the interview between Ellen Degeneres and Hillary Clinton which downloaded from Youtube website with the duration 19:11 minutes. The data are analyzed based on the theory of Conversation Analysis that proposed by Paltridge. The results of this research are, the interviewer (Ellen Degeneres) used all of the aspects of conversational interactions in giving and responding the questions to interviewees. On the other hand, the interviewees (Hillary Clinton) used Adjacency Pairs, Preference Organization, Turn Taking, Feedback and Repair. But Opening and Closing Conversation are not used by the interviewees throughout the conversation. So, five of seven aspects of conversational interactions in conversation are applied. Those aspects of conversational interactions are realized in the conversation with different realization. Those aspects of conversational interactions are realized in this conversation because it is the standard in conversation and the interviewer and interviewees applied the aspects of conversational interactions in order to seek the information from the interviewees, to give the clarification of the issues and to make a good communication in that conversation.